Occupational mismatch in the labour market of selected EU countries - Alka Obadić; Viktor Viljevac (Ekonomski Vjesnik)
Purpose: This paper aims to examine the occupational structures of selected EU member countries and assess their compatibility with the labour market demands, aiming to identify potential structural mismatches. The search evaluates the alignment between existing knowledge and skills in specific qualifications and those required by employers, utilizing disaggregated data from registered employment offices in Austria, Croatia, Slovenia, and Spain, spanning from 2010 to 2022. Methodology: Methodologically, the study uses Beveridge curves, labour market tightness, and matching efficiency estimates to measure the matching needs of employers and unemployed job seekers within various occupation groups. The analysis focuses on the impact of economic downturns and fluctuations in unemployment rates on different occupation groups, with a particular emphasis on more complex and better-paid occupations. Results: Results indicate that workers in higher-skilled occupations may experience a more resilient position within the aggregate labour market trends. However, the study reveals that deviations from these trends among occupation groups are relatively minor, underscoring the substantial influence of overall labour market conditions on all segments. Conclusion: The research finds that differences in occupation groups have a limited impact on the broader labour market trends. Regardless of occupation complexity, improvements and deteriorations in labour market conditions affect all groups uniformly. These findings suggest a nuanced interplay between occupational structures and aggregate labour market dynamics, emphasising the need for comprehensive policy considerations to address potential mismatches and promote overall labour market efficiency.